Role of Brassinolide in Fruit Growth, Development, Quality and Cracking of Litchi Cv. Bombai Grown in New Alluvial Zone of West Bengal - Ghosh, Tamashree; Panja, Payel; Sau, Sayan; Datta, Pallab (International Journal of Bio-resource and Stress Management, 2022)
Bombai’ is a popular litchi variety of West Bengal but susceptible to fruit cracking which reduces the market price. Till now numbers of research trial conducted in litchi with different chemicals but reports on impact of application of brassinolide in reduction of fruit cracking maintaining quality attributes are limited. Therefore, an experiment was conducted during January-May of 2019–20 at the Experimental Farm of Horticultural Research station, Mondouri, Bidhan Chandra Krishi Viswavidayala, Nadia, West Bengal, India to evaluate the effect of different dose of brassinolide on fruit yield, quality and reduction of cracking in litchi. The experiment was laid out in randomized block design comprising five treatments of brassinolide [T1: Brassinolide (0.5 mg l-1), T2: Brassinolide (1.0 mg l-1), T3: Brassinolide (1.5 mg l-1), T4: Brassinolide (2.0 mg l-1) and T5: Control (water spray)] with four replication/treatment. The solutions were applied two times; first before anthesis and another at 15 days after anthesis. Result revealed that brassinolide increased the number of fruits per panicle and significantly increased individual fruit weight, length, diameter, and yield. Among different treatments, brassinolides at 1 mg l-1 (two-time application i.e., 15 days before and after anthesis) is identified to be superior considering all qualitative aspects i.e., maximum fruit weight (26.40 g), fruit length (5.15 cm) and yield (95.88 kg plant-1). This treatment also exhibited maximum TSS (21.22°Brix), total sugar (14.11%), ascorbic acid (37.42 mg 100 g-1) and anthocyanin (23.13 mg 100 g-1) content with minimum (9.12%) fruit cracking. The control treatments registered minimum values for all parameters.